The greatness of Mir Anis as an Obituary Writer - karim, Naila Abdul; Abbas, Qamar; Bano, Saira (sourcecoder, 2024)
Mir Anis is considered among the top poets of Urdu. Mir Anis gave moral elevation to Urdu literature through his martyrs. He expanded the eulogy so much that it proved to be a unique example of poetry, visual art and thought. Mir Anis is the king of elegies. Therefore, it is important to enlighten the readers with the height of Anis's thought and art. Anis's poetry has an abundance of surprising expressions. In which the language is mastered. So first of all it is important to keep this environment in mind. In which Anis breathed and in which he began to write and read elegies and took all the manners necessary to impress an audience. In this paper also, in the context of Anis's home environment, his living conditions, poetic greatness and the perfection of Anis's art have been reviewed.